Iodine(III)-mediated halogenations of acyclic monoterpenoids - Peilleron, Laure; Grayfer, Tatyana D.; Dubois, Joëlle; Dodd, Robert H.; Cariou, Kevin (Beilstein Journal of Organic Chemistry, 2018)
Five different halofunctionalizations of acyclic monoterpenoids were performed using a combination of a hypervalent iodine(III) reagent and a halide salt. In this manner, the dibromination, the bromo(trifluoro)acetoxylation, the bromohydroxylation, the iodo(trifluoro)acetoxylation or the ene-type chlorination of the distal trisubstituted double bond occurred with excellent selectivity and moderate to good yields.
Keywords: halogenation; hypervalent iodine; monoterpenes

(untitled) - Agarwal, V.; Miles, Z. D.; Winter, J. M.; Eustáquio, A. S.; El Gamal, A. A.; Moore, B. S. (Chem. Rev., 2017)

(untitled) - Reddy, P.; Urban, S. (Phytochemistry, 2009)

(untitled) - Sun, J.-F.; Huang, H.; Chai, X.-Y.; Yang, X.-W.; Meng, L.; Huang, C.-G.; Zhou, X.-F.; Yang, B.; Hu, J.; Chen, X.-Q.; Lei, H.; Wang, L.; et al. (Tetrahedron, 2011)

(untitled) - Kubanek, J.; Prusak, A. C.; Snell, T. W.; Giese, R. A.; Hardcastle, K. I.; Fairchild, C. R.; Aalbersberg, W.; Raventos-Suarez, C.; Hay, M. E. (Org. Lett., 2005)

(untitled) - Burreson, J. B.; Woolard, F. X.; Moore, R. E. (Chem. Lett., 1975)

(untitled) - Yoshimura, A.; Zhdankin, V. V. (Chem. Rev., 2016)

(untitled) - Brown, M.; Farid, U.; Wirth, T. (Synlett, 2013)

(untitled) - Singh, F. V.; Wirth, T. (Chem. – Asian J., 2014)

(untitled) - Martín Romero, R.; Wöste, T. H.; Muñiz, K. (Chem. – Asian J., 2014)

(untitled) - Arnold, A. M.; Ulmer, A.; Gulder, T. (Chem. – Eur. J., 2016)

(untitled) - Nocquet-Thibault, S.; Retailleau, P.; Cariou, K.; Dodd, R. H. (Org. Lett., 2013)

(untitled) - Nocquet-Thibault, S.; Minard, C.; Retailleau, P.; Cariou, K.; Dodd, R. H. (Tetrahedron, 2014)

(untitled) - Beltran, R.; Nocquet-Thibault, S.; Blanchard, F.; Dodd, R. H.; Cariou, K. (Org. Biomol. Chem., 2016)

(untitled) - Nocquet-Thibault, S.; Rayar, A.; Retailleau, P.; Cariou, K.; Dodd, R. H. (Chem. – Eur. J., 2015)

(untitled) - Daniel, M.; Blanchard, F.; Nocquet-Thibault, S.; Cariou, K.; Dodd, R. H. (J. Org. Chem., 2015)

(untitled) - Grayfer, T. D.; Retailleau, P.; Dodd, R. H.; Dubois, J.; Cariou, K. (Org. Lett., 2017)

(untitled) - Demertzidou, V. P.; Pappa, S.; Sarli, V.; Zografos, A. L. (J. Org. Chem., 2017)

(untitled) - Hegde, S. G.; Vogel, M. K.; Saddler, J.; Hrinyo, T.; Rockwell, N.; Haynes, R.; Oliver, M.; Wolinsky, J. (Tetrahedron Lett., 1980)

(untitled) - Zhou, Z.; He, X. (Synthesis, 2011)

(untitled) - Hokamp, T.; Storm, A. T.; Yusubov, M.; Wirth, T. (Synlett, 2018)

(untitled) - Smietana, M.; Gouverneur, V.; Mioskowski, C. (Tetrahedron Lett., 2000)

(untitled) - Pan, Z.; Liu, X.; Liu, W.; Liang, Y. (Synthesis, 2005)

(untitled) - Wilson, C. V. (Org. React., 1957)

(untitled) - Courtneidge, J. L.; Lusztyk, J.; Pagé, D. (Tetrahedron Lett., 1994)

(untitled) - Merkushev, E. B.; Simakhina, N. D.; Koveshnikova, G. M. (Synthesis, 1980)

(untitled) - Barnett, J. R.; Andrews, L. J.; Keefer, R. M. (J. Am. Chem. Soc., 1972)

(untitled) - Kato, T.; Ichinose, I. (J. Chem. Soc., Perkin Trans. 1, 1980)

(untitled) - Monenschein, H.; Sourkouni-Argirusi, G.; Schubothe, K. M.; O’Hare, T.; Kirschning, A. (Org. Lett., 1999)

(untitled) - Muñiz, K.; García, B.; Martínez, C.; Piccinelli, A. (Chem. – Eur. J., 2017)

(untitled) - Van Tamelen, E. E. (Acc. Chem. Res., 1968)